PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI, DAN BUDAYA KERJA TERHADAP KOMITMEN PEGAWAI DAN DAMPAKNYA PADA KINERJA (Sensus pada Pegawai Negeri Sipil Eselon III di Lingkungan Dinas Pemerintah Kab. Tasikmalaya) - Tia Ernawati (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2020)
Abstract The purpose of this study was to determine and analyze the influence of the Leadership Style, Communication, Work Culture and Commitment of Employees on employee performance both partially and simultaneously on the Tasikmalaya Regency Government Office Environment. The object of study was the Environmental Officer of the Tasikmalaya Regency Government Office. The research method used is path analysis. Data collection was obtained through observation, questionnaires and literature study. The population in this study was 78 Echelon III employees. Leadership Style, Communication, Work Culture, Commitment of Employees and Performance of Employees in the Tasikmalaya Regency Government Offices are quite good. Leadership Style, Communication and Work Culture influence the Commitment of Employees both simultaneously and partially on the Environmental Employees of the Tasikmalaya Regency Government Office. The Leadership Style, Communication, Work Culture and Commitment of Employees have an effect on performance both partially and simultaneously on the Environmental Staff of the Tasikmalaya Regency Government Office. Keywords: Leadership Style, Communication, Work Culture, Commitment of Employees and Performance